Entrepreneurship, firm size and the structure of the Italian economy - Pellegrino Manfra (The Journal of Entrepreneurial Finance and Business Ventures, 2002)
Since World War II, Italy.s economic growth has been one of the highest in the world. The objective of this study is to examine the structure of the Italian economy and causes of this growth. It was found that small and medium-sized firms, most of them family-owned, have been the dynamic force behind the country.s extraordinary economic performance. The vital role of the family and that of the entrepreneur . as the supreme spirit of enterprise and initiative - has been paramount in this process. Production by small and medium-sized firms have concentrated in a specific geographical area called industrial districts and are capable of great cooperation with other firms, leading to increased production, efficiency and employment. In addition, it was found that small Italian firms have been very successful in the age of globalization, better able to take advantage of their small size by means of flexible strategies to innovate, invest and increase their export. Contrary to conventional wisdom, modernization theories (so widespread in the 1950s and 1960s) indicate that large firms have been models for growth in other industrialized countries and have exerted a passive role in the structure and development of the Italian economy.
Keywords: 650